Why is social isolation among older adults associated with depressive symptoms?: the mediating role of out-of-home physical activity - Herbolsheimer, Florian; Ungar, Nadine; Peter, Richard (International journal of behavioral medicine, 2018)
Background Social networks are known to be a key factor associated with late-life depression. However, there is limited knowledge about the pathways linking social isolation to mental health. It has been proposed that health-related behaviors such as physical activity represent one pathway. This study examines the way out-of-home physical activity mediates between social isolation and depressive symptoms in older adults.Methods A subsample of 334 older adults from the ActiFE Ulm study, Germany, was randomly selected. Older adults (M = 72.6 years; 60.8% male) were interviewed at baseline and 3 years later. Depressive symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS). Social isolation was measured using the Lubben Social Network Scale (LSNS-6). Physical activity was measured by an accelerometer (activPAL) over 1 week. To identify out-of-home physical activity, a contemporary physical activity diary classified out-of-home physical activity.Results A cross-lagged structural equation model supported an indirect effect (β = .014, 95% CI .002 to .039) which means that being socially isolated was associated with lower levels of out-of-home physical activity, and this predicted more depressive symptoms after 3 years. However, no direct relationship was observed between social isolation from friends and neighbors at the baseline and depressive symptoms 3 years later.Conclusions Utilizing a longitudinal study design and accounting for reverse causality, this study extends prior work linking social isolation to depression by showing that a variety of neighbor and friendship ties are linked to fewer depressive symptoms by providing occasions for out-of-home physical activity.
First Online: 22 October 2018
Gesehen am 18.12.2019